2011
DOI: 10.5194/acp-11-103-2011
|View full text |Cite
|
Sign up to set email alerts
|

Downslope windstorm in Iceland – WRF/MM5 model comparison

Abstract: Abstract.A severe windstorm downstream of Mt. Öraefa-jökull in Southeast Iceland is simulated on a grid of 1 km horizontal resolution by using the PSU/NCAR MM5 model and the Advanced Research WRF model. Both models are run with a new, two equation planetary boundary layer (PBL) scheme as well as the ETA/MYJ PBL schemes. The storm is also simulated using six different micro-physics schemes in combination with the MYJ PBL scheme in WRF, as well as one "dry" run. Output from a 3 km MM5 domain simulation is used t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…• No simplifying (linear) approximations applied to the model equations of motion; the most hazardous mountain wave flows are highly non-linear, e.g., rotors and hydraulic jumps/wave breaking • Realistic initial and boundary conditions, data assimilation, representation of convergence and convection; problems can occur in 3DVOM when there is significant horizontal variation in conditions and atmospheric forcing (e.g., trough or low centre within the domain), since it is initialised by a single profile • Thorough representation of moist processes (noting that the U.K. has a very moist climate with cloud and rainfall common); 3DVOM is a dry model, but in reality, reversible latent heating (cloud formation and evaporation) effects favour flow over terrain rather than blocking, also affecting wave amplitude [58]; meanwhile, irreversible latent heating effects (e.g., upslope rainfall) modify the stability profile and, hence, the wave response [59][60][61][62]; further, any orographically-triggered deep convection will negate wave activity • More sophisticated boundary layer scheme; the boundary layer is known to impact lee wave generation and downwind decay [63][64][65], while the performance of the boundary layer scheme also decides the accuracy of forecast lee wave impacts on near-surface winds [13,44] • Direct simulation of the diurnal cycle through radiation, surface and boundary layer parametrisations, including for instance nocturnal stable boundary layers; boundary layer stability strongly affects wave propagation and lee wave decay [64] • Full and contiguous coverage of the U.K. (and eventually beyond, as future computing resources allow) • Lee wave impacts become prognostic; the interplay of lee waves with the atmospheric environment in which they form, including other weather phenomena, is represented • Access to a comprehensive, standardised set of diagnostics, long-term central archiving…”
Section: Discussionmentioning
confidence: 99%
“…• No simplifying (linear) approximations applied to the model equations of motion; the most hazardous mountain wave flows are highly non-linear, e.g., rotors and hydraulic jumps/wave breaking • Realistic initial and boundary conditions, data assimilation, representation of convergence and convection; problems can occur in 3DVOM when there is significant horizontal variation in conditions and atmospheric forcing (e.g., trough or low centre within the domain), since it is initialised by a single profile • Thorough representation of moist processes (noting that the U.K. has a very moist climate with cloud and rainfall common); 3DVOM is a dry model, but in reality, reversible latent heating (cloud formation and evaporation) effects favour flow over terrain rather than blocking, also affecting wave amplitude [58]; meanwhile, irreversible latent heating effects (e.g., upslope rainfall) modify the stability profile and, hence, the wave response [59][60][61][62]; further, any orographically-triggered deep convection will negate wave activity • More sophisticated boundary layer scheme; the boundary layer is known to impact lee wave generation and downwind decay [63][64][65], while the performance of the boundary layer scheme also decides the accuracy of forecast lee wave impacts on near-surface winds [13,44] • Direct simulation of the diurnal cycle through radiation, surface and boundary layer parametrisations, including for instance nocturnal stable boundary layers; boundary layer stability strongly affects wave propagation and lee wave decay [64] • Full and contiguous coverage of the U.K. (and eventually beyond, as future computing resources allow) • Lee wave impacts become prognostic; the interplay of lee waves with the atmospheric environment in which they form, including other weather phenomena, is represented • Access to a comprehensive, standardised set of diagnostics, long-term central archiving…”
Section: Discussionmentioning
confidence: 99%
“…Among the ma jor fac tors af fect ing the ac cu racy of sim u la tion of the fields of me te o ro log i cal pa ram e ters dur ing bora that are con sid ered in the pres ent pa per and in some other re searches [15,18], the hor i zon tal res o lu tion of the model, the or der of discretization of advective terms, the parameterization of cloud microphysics, of tur bu lence, and of at mo spheric bound ary layer should be noted.…”
Section: De Scrip Tion Of Nu Mer I Cal Ex Per I Mentsmentioning
confidence: 99%
“…Pa per [18] stud ies the ef fects that dif fer ent schemes of parameterization of microphysical pro cesses in clouds may have on the fore cast of downslope wind storms. Basing on the results shown in [18], we used the WSM 6 scheme and Thomp son scheme (be ing the full est and most com plex). Be sides, pa per [18] found that the Thomp son scheme is the best in fore cast ing downslope wind storms.…”
Section: De Scrip Tion Of Nu Mer I Cal Ex Per I Mentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The different nature of the two categories of boundary layer schemes (local versus nonlocal turbulent diffusion), may affect the mesoscale flows well as the vertical thermal gradient of the atmosphere . Their advantages and disadvantages were examined in some recent studies (e.g., Shin and Hong, 2011;Rögnvaldsson et al, 2011), exploiting the different parametrization schemes options provided with the WRF model. Also, for mesoscale simulation with horizontal scales of O(1 km), large eddies begin to blend with the parametrized mixing from the PBL scheme (Stensrud, 2007).…”
Section: Detailed Evolution Of the Marine Boundary Layer: A Les Studymentioning
confidence: 99%